Localized Castleman’s Disease in Retroperitoneum Mimicking Broad Ligament Leiomyoma – a Diagnostic Challenge - Gon, S; Mallik, D; Bhattacharya, A; Majumdar, B; Sengupta, M (Nepal Journal of Obstetrics and Gynaecology, 2016)
Primary retroperitoneal tumours pose a diagnostic dilemma and therapeutic challenges because of their location and late detection. Localized Castleman Disease (CD) in retroperitoneal location is a rare occurrence, with incidence of only 4% cases occurring in diverse locations like retroperitoneum. A rare case of unicentric localized Castleman Disease localized in broad ligament is hereby reported which was clinically & radiologically suspected as broad ligament leiomyoma but finally diagnosed as Castleman’s Disease, hyaline vascular type in a young female posing a diagnostic challenge both for the pathologist and clinician. Definite diagnosis is essential as complete surgical excision in case of unicentric Castleman’s Disease has good prognosis after resection.